1.1.4 Nonconventional Reaction Media: Hydroformylation, Carbonylation, and Hydroxycarbonylation of Alkenes - Mortreux,A.; Sauthier,M.; Monflier,E.; Tilloy,S. (C-1 Building Blocks in Organic Synthesis 1, 2014)
This chapter focuses on catalytic reactions involving the use of carbon monoxide and alkenes together with tertiary substrates such as hydrogen, alcohols, amines, or water where the catalyst recovery and recycling has been emphasized via the use of biphasic media. These atom-economical catalytic reactions result in the synthesis of aldehydes, esters, amines, and carboxylic acids, as well as polyketones, where the activity and regioselectivity concerns have been addressed.
Keywords: hydroformylation; hydroesterification; carbonylation; hydroxycarbonylation; carbon monoxide; biphasic catalysis; ionic liquid; water-soluble ligands; phosphines; cyclodextrins; recycling; regioselectivity